Identification of saltwater intrusion/assessment scheme in groundwater using the role of empirical knowledge - Mohd Isa, Noorain; Aris, Ahmad Zaharin (Elsevier, 2015)
Kapas Island depends solely on groundwater as the major source of freshwater supply for the drinking and domestic purposes. High consumption of fresh groundwater leads to deterioration of its quality. In order to overcome this issue, a monitoring of groundwater sampling was conducted. A total of 216 groundwater samples were collected in different monsoon and were tested for physic-chemical parameters. Pre-monsoon was recorded Na-rich type while post-monsoon was dominated by Ca-rich type. The level of saline interferences was identified using ionic strength and Cl concentrations where it reveals the fresh to moderate groundwater condition